Preoperative Prediction of Lymph Node Metastasis of Pancreatic Ductal Adenocarcinoma Based on a Radiomics Nomogram of Dual-Parametric MRI Imaging - Shi, Lin; Wang, Ling; Wu, Cuiyun; Wei, Yuguo; Zhang, Yang; Chen, Junfa (Frontiers in Oncology, 2022)
Purpose: This study aims to uncover and validate an MRI-based radiomics nomogram for the preoperative detection of lymph node metastasis (LNM) in pancreatic ductal adenocarcinoma (PDAC) patients. Materials and Methods: We retrospectively collected 141 patients with PDAC confirmed by pathology, who underwent preoperative T2-weighted imaging (T2WI) and portal venous phase (PVP) contrast-enhanced T1-weighted imaging (T1WI) scans between January 2017 and December 2021. The patients were randomly divided into training (n = 98) and validation (n = 43) cohorts at a ratio of 7:3. For each sequence, 1037 radiomics features were extracted and analyzed. After applying the gradient-boosting decision tree (GBDT), the key MRI radiomics features were selected. We calculated three radiomics scores (rad-score 1 for PVP, rad-score 2 for T2WI, and rad-score 3 for T2WI combined with PVP). Rad-score 3 and clinical independent risk factors were combined to construct a nomogram for the prediction of LNM of PDAC by multivariable logistic regression analysis. The predictive performances of rad-scores and the nomogram were assessed by the area under the operating characteristic curve (AUC), and the clinical utility of the radiomics nomogram was assessed by decision curve analysis (DCA). Results: Six radiomics features of T2WI, 8 radiomics features of PVP and 10 radiomics features of T2WI combined with PVP were identified to be associated with LNM. Multivariate logistic regression analysis showed that rad-score 3 and MRI-reported LN status were independent predictors. In the training and validation cohorts, the AUCs of rad-score 1, rad-score 2 and rad-score 3 were 0.769 and 0.751,0.807 and 0.784, and 0.834 and 0.807, respectively. The predictive value of rad-score 3 was similar to that of rad-score 1 and rad-score 2 in both the training and validation cohorts (P > 0.05). The radiomics nomogram constructed by rad-score 3 and MRI-reported LN status showed encouraging clinical benefit with an AUC of 0.845 for the training cohort and 0.816 for validation. Conclusions: The radiomics nomogram derived from rad-score based on features from MRI images and MRI-reported lymph status shows outstanding performance for the preoperative prediction of LNM in PDAC.